2022
DOI: 10.1186/s10020-022-00531-3
|View full text |Cite
|
Sign up to set email alerts
|

LINC00240/miR-155 axis regulates function of trophoblasts and M2 macrophage polarization via modulating oxidative stress-induced pyroptosis in preeclampsia

Abstract: Background This study aimed to investigate the effects of LINC00240/miR-155/Nrf2 axis on trophoblast function and macrophage polarization in the pathogenesis of preeclampsia. Methods Bindings between LINC00240, miR-155 and Nrf2 were validated by dual luciferase reporter assay or RNA-immunoprecipitation. Cell proliferation, migration, invasion, and pyroptosis were detected by CCK-8, clone formation, wound healing, Transwell system, and flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…A direct association between LINC00240 and miR-155-5p was identified in this study, and miR-155-5p functioned as a downstream molecule of LINC00240 to mediate Th9 differentiation. Interestingly, a more recent study has demonstrated that LINC00240 binds to miR-155-5p directly, and LINC00240/miR-155-5p/Nrf2 axis contributes to the pathogenesis of preeclampsia [32], indicating the diverse function of LINC00240/miR-155-5p axis in different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A direct association between LINC00240 and miR-155-5p was identified in this study, and miR-155-5p functioned as a downstream molecule of LINC00240 to mediate Th9 differentiation. Interestingly, a more recent study has demonstrated that LINC00240 binds to miR-155-5p directly, and LINC00240/miR-155-5p/Nrf2 axis contributes to the pathogenesis of preeclampsia [32], indicating the diverse function of LINC00240/miR-155-5p axis in different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis, another cell death pathway, has been observed in primary human trophoblasts under pathophysiological condition [ 42 ]. Enhanced oxidative stress or NLRP3-inflammasome-activation-induced pyroptosis inhibit trophoblast cell proliferation, migration and invasion in both in vitro and in vivo models of preeclampsia [ 62 , 63 ] (Fig. 2B ).…”
Section: Involvement Of Rcd At the Maternal-fetal Interface In Pregnancymentioning
confidence: 99%
“…Oxidative stress-induced pyroptosis inhibited M2 macrophage polarization [ 62 ]. In women experiencing spontaneous preterm labor, decidual macrophages undergo pyroptosis, as evidenced by the presence of active caspase-1, GSDMD and mature IL-1β [ 82 ].…”
Section: Involvement Of Rcd At the Maternal-fetal Interface In Pregnancymentioning
confidence: 99%
“…On the contrary, LINC00240 is lowlyexpressed in the placenta tissues of PE patients. The downregulated LINC00240 aggravates oxidative stress-induced pyroptosis through increasing miR-155 and reducing Nrf2 expression, and LINC00240 overexpression mitigates the pyroptotic death of trophoblasts (58). Additionally, the lowlyexpressed miR-520c-3p is observed in the placental tissues of PE patients and H/R-treated trophoblasts, and melatonin may suppress trophoblasts pyroptosis via modulating miR-520c-3p/SETD7 axis (93).…”
Section: The Role Of Pyroptosis In Trophoblastsmentioning
confidence: 99%